STUDY OF DETERMINING THE OPTIMUM LOCATION OF CENTRALIZED TRANSFORMERS AT THE FACULTY OF ENGINEERING TANJUNGPURA UNIVERSITY - Syarif, Asdam; Fitriah, Fitriah; Kurnianto, Rudi (Faculty of Engineering, Universitas Tanjungpura, 2024)
The development of electricity at Tanjungpura University, especially in the Faculty of Engineering, is very rapid in line with the development of new buildings and facilities in the campus environment which require a large electricity supply. The increasing use of electrical energy on the user side results in inappropriate loading. If this situation persists for a long time it will result in overload. For this reason, the researchers planned a centralized transformer based on minimal voltage drops and ideal transformer loading which refers to SPLN 72.1987. Determining the optimal location of this transformer uses literature study methods, field observations and descriptive analytics. In determining the location of a centralized transformer, several calculations are carried out, namely full load current calculation, distribution transformer loading calculation, manual voltage drop calculation and voltage drop simulation, transformer capacity calculation, voltage drop analysis over network area, voltage drop condition over network area, transformer layout calculation. , and calculate the type of cable to be used. By carrying out this study to determine the optimal location of the transformer, based on calculations and analysis, it can be determined that the ideal transformer capacity is 3000 kVA (3000000 VA), the loading results are 19,7%, the voltage drop is 0.44%, and the cable cross-sectional area is 150 mm2.